DSS controlling a machine manufacturing - Khavina, I. P.; Lymarenko, V. V. (Baltija Publishing, Latvia, 2019)
The proposed methods and approaches, despite the complexity of their implementation, have shown good results for this task and the promise of their application in other areas of science and technology. In the future, it is planned to conduct a study to simulate the work of intelligent agents in emergency situations. In the future, it is planned to conduct a study to simulate the work of intelligent agents in emergency situations.
Keywords: decision support systems; Artificial Intelligence; multiagent systems; technological process; cutting; multiparametrical optimization problem